Cover Image, Volume 1436, Issue 1. Issue 1 (30th January 2019) - Miralles, Diego G.; Gentine, Pierre; Seneviratne, Sonia I.; Teuling, Adriaan J.
Abstract : On the cover : The cover image, submitted by Diego G. Miralles et al., is from the Perspective "Land‐atmospheric feedbacks during droughts and heatwaves: state of the science and current challenges, "https://doi.org/10.1111/nyas.13912 .